A comparative analysis of the treatment NINA debtors in South Africa and Scotland during the Covid-19 pandemic - Van Wyk, Jani Sani (University of Pretoria, 2024)
Mini Dissertation (LLM (Insolvency Law))--University of Pretoria, 2023.